2019
DOI: 10.1186/s13047-019-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of non‐surgical interventions for common plantar digital compressive neuropathy (Morton's neuroma): a systematic review and meta‐analysis

Abstract: Background Morton’s neuroma (MN) is a compressive neuropathy of the common plantar digital nerve. It is a common compressive neuropathy often causing significant pain which limits footwear choices and weight bearing activities. This paper aims to review non-surgical interventions for MN, to evaluate the evidence base for the clinical management of MN. Methods Electronic biomedical databases (CINAHL, EMBASE, MEDLINE and Cochrane) were searched to January 2018 for studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 85 publications
(420 reference statements)
4
43
0
4
Order By: Relevance
“…More recently, one randomized study indicated that though both treatments improved outcomes for 18 months, corticosteroids had a greater improvement than PRP within 1 month of injection, and PRP had a more positive effect than ICS at 6-, 12-, and 18-month follow-ups [38]. Conversely, two other studies found that ICS and PRP both improved outcomes up to 16 weeks and 6 months, respectively, with no difference between level of improvement due to the two treatments [8,9].…”
Section: Plantar Fasciitismentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, one randomized study indicated that though both treatments improved outcomes for 18 months, corticosteroids had a greater improvement than PRP within 1 month of injection, and PRP had a more positive effect than ICS at 6-, 12-, and 18-month follow-ups [38]. Conversely, two other studies found that ICS and PRP both improved outcomes up to 16 weeks and 6 months, respectively, with no difference between level of improvement due to the two treatments [8,9].…”
Section: Plantar Fasciitismentioning
confidence: 99%
“…Diagnosis of MN can also be confirmed with the Mulder maneuver, where pressure and tightening is exerted on the metatarsals, resulting in pain and a distinct clicking or the Silfverskiöld test to assess gastrocnemius muscle tightness are useful in diagnosing MN [5][6][7]. Surgical treatment of MN is traditionally a neurectomy; however, non-surgical treatments first are now becoming more recommended [5,8]. A non-surgical option is preferred due to the large spectrum of potential causes of MN, patients declining surgical options, or not being suitable for surgery due to contraindications [5,8].…”
Section: Morton's Neuromamentioning
confidence: 99%
See 1 more Smart Citation
“…Bennett et al 1995 noted that 85% of 115 patients found that they had improvement from non-surgical treatment and just 21% required surgical excision [4]. However, in a systematic review of non-surgical interventions Matthews et al 2019 found only limited evidence for non-surgical treatment though it was still recommended that non-surgical treatment should always be attempted prior to surgery [11,12,13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Conservative measures such as steroid injection and mobilization have shown some benefit. [20] Surgical resection is often necessary. [21].…”
Section: Interdigital Neuralgiamentioning
confidence: 99%